Georgia Architectural and Historic Properties Survey of 209 Chandler St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 209 Chandler St., Valdosta, Ga., December 1980. One story rectangular plan house. Tin, gabled roof. Square posts at porch. Interior chimney. Board and batten siding. Double hung sash windows with 6/6 lights. Set on brick piers. Fair condition. Date of Construction: N/A. The only board and batten sided house within miles. Significant as part of a potential N.R. district which covers 4 or 5 blocks.
Georgia Architectural and Historic Properties Survey of 209 Chandler St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 77.9 MB (81,787,946 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)